1992
DOI: 10.1096/fasebj.6.2.1537469
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome P450 may regulate plasma membrane Ca 2+ permeability according to the filling state of the intracellular Ca 2+ stores

Abstract: The filling state of the intracellular Ca2+ stores of rat thymocytes regulates plasma membrane permeability to Mn2+, used here as a Ca2+ surrogate for plasma membrane Ca2+ channels. Emptying of the Ca2+ stores accelerated Mn2+ entry about 10-fold, and refilling with Ca2+ restored low Mn2+ permeability. The acceleration of Mn2+ entry observed in cells with empty intracellular Ca2+ stores was prevented by cytochrome P450 inhibitors. Imidazole antimycotics, especially econazole and miconazole, were the most poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
0
1

Year Published

1993
1993
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(72 citation statements)
references
References 35 publications
2
68
0
1
Order By: Relevance
“…We have observed that the calmodulin inhibitor W-7 depleted intracellular Ca2+ pools and decreased Ca2+ influx in FRTL-5 cells [19]. A possible role for calmodulin in regulating Ca2+ fluxes has been suggested in some recent reports [33,34]. However, both SP and SPC enhanced Ca2+ entry in our cells, which is not expected if the effects of these compounds were the result of inhibition of calmodulin.…”
Section: Effectsmentioning
confidence: 51%
“…We have observed that the calmodulin inhibitor W-7 depleted intracellular Ca2+ pools and decreased Ca2+ influx in FRTL-5 cells [19]. A possible role for calmodulin in regulating Ca2+ fluxes has been suggested in some recent reports [33,34]. However, both SP and SPC enhanced Ca2+ entry in our cells, which is not expected if the effects of these compounds were the result of inhibition of calmodulin.…”
Section: Effectsmentioning
confidence: 51%
“…CLT has been shown to have a multiplicity of effects on cell proliferation (32), steroid metabolism (33)(34)(35), and sickle cell dehydration (36,37). The mechanism of these actions has been variously attributed to its inhibitory effect on cytochrome P450-dependent enzymes (38), sarcoplasmic reticulum Ca 2ϩ pump (39), capacitative Ca 2ϩ channels (32,40,41), and the intermediate-conductance Gardos channel (18). The diversity of reported actions suggests that CLT may act independently on a surprising variety of targets.…”
Section: Discussionmentioning
confidence: 99%
“…This metabolic response, as well as the documented effects of epoxygenase products on renal H20 and Na + transport and, in particular, the early demonstration of an inhibition of Na+ reabsorption in the isolated cortical collecting tubule by EETs (4, 7) lead us to propose that the epoxygenase may be part of the adaptive response of the kidney to excess Na+ intake. Clotrimazole and ketoconazole, powerful inhibitors of microsomal cytochrome P450 (18), have been used in the past to characterize the functional significance of the hemoprotein in several isolated cell or whole organ preparations (4,27,28). We have shown, using rat liver microsomal fractions, that clotrimazole selectively inhibits the arachidonic acid epoxygenase and that it is a substantially less effective inhibitor of the arachidonic acid w/w-1 oxygenase reaction (18).…”
Section: Discussionmentioning
confidence: 99%